Sandalwood (Santalum album) growth and farming success strengthen its natural conservation in the Timor Island, Indonesia - YOSEPH NAHAK SERAN; SUDARTO SUDARTO; LUCHMAN HAKIM; ENDANG ARISOESILANINGSIH (Society for Indonesian Biodiversity, 2018)
Seran YN, Sudarto, Hakim L, Arisoesilaningsih E. 2018. Sandalwood (Santalum album) growth and farming success strengthen its natural conservation in the Timor Island, Indonesia. Biodiversitas 19: 1586-1592. Sandalwood (Santalum album L.) is a unique plant of the East Nusa Tenggara (NTT) Province of Indonesia and locally known as the unity symbol woody fragrance (hau meni). The study aimed to compare growth quality of trees grown in plantations and forests in the districts of North Central Timor (TTU) and South Central Timor (TTS). Vegetation analysis was held by purposive sampling in eight sites comprising 87 plots. Plots sizes were 20x20 m2 for trees, 10x10 m2 for poles, and 5x5 m2 for saplings. Variables observed in each plot included density, trunk diameter, height, crown quality, and vitality. Data were analyzed by descriptive and multivariate statistics. The results showed that the growth of sandalwoods varied spatially in all study sites and was classified into five groups. Two plantations in TTS District showed better trees growth quality compared to those in TTU. Higher saplings and poles density were found in two sites, a plantation and a forest in TTU plantation, and in a forest in TTS. However higher vitality were found in two plantations, each one in TTS and TTU. Inferior growth was observed in Nununamat plantation. Farmers had a significant role in strengthening sandalwood conservation in two districts as shown by their successful farming and trees growth quality that was similar to those in the forests.